سکھ مت کا تصور توحید اور اس پر اسلامی تعلیمات کے اثرات کا تجزیاتی مطالعہ (گرو گرنتھ صاحب کی روشنی میں): An analytical study of the concept of monotheism in Sikhism and Islamic influences on it - ahmed, sheraz (Al-Amīr Research Journal for Islamic Studies, 2020)
The basic concept of monotheism is found in the teachings of Guru Nanak. There are basically two doctrinal things in Sikhism. One is the belief in the oneness of God and the other is the promotion of human brotherhood. In Guru Granth Sahib, the words of some devotees also convey the idea of polytheistic beliefs. However, as far as the words and ideas of Guru Nanak are concerned, they seem to be safe from polytheism. According to Sikh Dharma, God is the Creator and Almighty of the world and he is eternal. Guru Nanak’s concept of God is similar to Islam’s concept of monotheism. The monotheism of Sikhism as a whole is between Islam and Hinduism. In addition to acknowledging the existence of God, Granth Sahib also acknowledges the greatness of the gods and goddesses. But Guru Nanak used to give the status of creatures to all these gods and goddesses. The philosophy of Wahdat-ul-Wujud is very strong in Sikhism. But in Islam and Sikhism there is a clear difference between the interpretations of the doctrine of Wahdat-ul-Wujud and Wahdat-ul-Shuhud. Undoubtedly, Guru Nanak was deeply influenced by the concept of monotheism in Islam. Similarly, other Gurus have also stated contradictory teachings in their discourse on monotheism in Granth Sahib.